A Case Report of Parkinsonâ€™s Disease in a 70 year Man With Myasthenia Gravis - Ahadi, Muhammad Yanuar; Hadi, Deby Wahyuning; Soemarno, Soemarno; Octavia, Evi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
AbstractBackground:. Neurodegenerative diseases such as Parkinsonâ€™s disease (PD) have increasing incidence, due to lifespan expansion. The association between PD and Myasthenia Gravis (MG) is uncommon, and so far, since 1987, 26 cases have been reported.Case presentation: This is a report of a 70-year-old man was referred into the hospital with ptosis, disfagia and dispnea. He was diagnosed with Suspected Myasthenia Gravis, Post Stroke Trombotik, Parkinsonâ€™s Disease and Hypertension. The patient was admitted to the outpatient unit, received of treatment Pyridostigmine, Clopidogrel, Trihexylphenidil, Vitamine B1, Vitaminie B6, Vitamine B12 and Levodopa-Benserazide .Discussion: Treatment guidelines by using some guidelines are also drug doses and do not have adverse side reactions during treatment.Conclusion:. PD and MG very rarely occur together. case report or a series of brief cases reported in the literature, it is very important not to miss the diagnosis of MG in patients with PD, because the treatment implications are very important and greatly influence the prognosis. More basic research needs to be done to understand the pathogenesis of both diseases, to provide more therapeutic options and possibly change the approach of the patient, whose quality of life is determined by these two neurological diseases, which have an increased impact on increasing disabilityKey words: Parkinson disease; Myasthenia gravis; coâ€occurrence; case report.